Stress and the working poor - Řimnáčová, Zuzana; Kajanová, Alena (Walter de Gruyter GmbH, 2019)
The working poor are not a clearly defined group. There are still people who work full-time, but have incomes bordering on poverty level. They tend to remain in work despite their low wages simply to avoid becoming unemployed and risk social exclusion. However, working in low-income jobs for long periods creates stress and gives rise to further problems. Stress affects sleep patterns and leads to problems associated with food intake and nutrition, and thus to disorders of the gastrointestinal system. Cardiovascular and neurological disorders may occur too. A lack of finances, and the stresses stemming from that are statistically significant and a strong predictor of a worse mental state. There is also a higher probability of psychosis occurring. All this affects the entire family, especially children. The inability to invest money and time in their development is another consequence.
Stres a pracující chudí
Keywords: stress; working poor; low income; health problems; stres; pracující chudí; nízký příjem; zdravotní problémy